Konsep Dan Implementasi Jaminan Fidusia Dalam Perjanjian Sewa Guna Usaha Kendaraan Bermotor - Anjar Kususiyanah (LP3M STITNU Al Hikmah Mojokerto, 2018)
Improved services and provision of convenience facilities held by market participants, rather than not risky for investment, therefore investors prefer a service product that has legality aspects. Leasing agreements are agreements where the price of goods can be paid in installments, while the goods can be handed over to buyer. Even though the goods have been handed over to the buyer, the ownership rights are still available to the seller so that the payment during the installment period is considered as a lease until all prices are met. Ownership of new goods is transferred to the buyer when the last installment has been paid by offering or not buying options. Because the buyer has not become the owner of the goods purchased, he is not allowed to sell or act other laws that are required to be the owner of the goods, such as multiplying, hypnotizing and others. If this is done, the buyer has committed no embezzlement.